2016
DOI: 10.21307/ane-2017-027
|View full text |Cite
|
Sign up to set email alerts
|

Age‑dependent concomitant changes in synaptic function and GABAergic pathway in the APP/PS1 mouse model

Abstract: Synaptic dysfunction is a well-documented manifestation in animal models of Alzheimer's disease pathology. In this context, numerous studies have documented reduction in the functionality of synapses in various models. In addition, recent research has shed more light on increased excitability and its link to seizures and seizure-like activities in AD patients as well as in mouse models. These reports of hyperexcitability contradict the observed reduction in synaptic function and have been suggested to be as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Originally developed as an AD mouse model, APP/PS1-Tg mice have also been recognized as a model of excitatory/inhibitory imbalance, including seizure-related sudden death 30 , 31 , 35 37 . The strain kept in our facility showed approximate 50% mortality over the first 3 months after birth.…”
Section: Resultsmentioning
confidence: 99%
“…Originally developed as an AD mouse model, APP/PS1-Tg mice have also been recognized as a model of excitatory/inhibitory imbalance, including seizure-related sudden death 30 , 31 , 35 37 . The strain kept in our facility showed approximate 50% mortality over the first 3 months after birth.…”
Section: Resultsmentioning
confidence: 99%
“…Aβ peptide is known to induce synaptic dysfunction during early stages of AD by deregulating molecular organization of the postsynaptic density (Liu et al, 2010;Oyelami et al, 2016). Because of this, we evaluated the levels of PSD-95, one of the major scaffolding protein in the excitatory postsynaptic density and a potent regulator of synaptic strength (Chen et al, 2011b), and the levels of the presynaptic component synaptophysin, which are known to be reduced in APP/PS1 mice at advanced stages of the neurodegenerative process (Woo et al, 2015;Mitew et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These potential diseasemodifying drugs fall into four categories: monoclonal antibodies, gamma secretase inhibitors, tau aggregation inhibitors, and symptomatic treatments. Some examples of previously failed clinical trials include (i) bapineuzumab, one of the first monoclonal amyloid-β antibodies to reach phase 3 clinical trials, but unfortunately was found to have no significant clinical benefit (Salloway et al, 2014), (ii) solanezumab, which despite demonstrating an excellent safety profile and low incidence of vasogenic edema, failed to meet primary and secondary endpoints in the phase2B-3A study (Doody et al, 2014;Siemers et al, 2016), (iii) crenezumab did not show a significant benefit in treatment in comparison to placebo in a phase 2 trial (Miller, 2012), and (iv) gantenerumab did not meet a significant clinical efficacy endpoint in phase 3 trials at its administered dosage (Ostrowitzki et al, 2017). However, more recently, Aducanumab, a human monoclonal antibody that is selective for aggregated forms of amyloid-β has been examined as a potential treatment for amyloid-β-associated pathologies.…”
Section: Treatment Strategies In Amyloid-β-related Admentioning
confidence: 99%